OPTIMAL TIME FOR RECOVERY AND CRYOPRESERVATION OF EPIDIDYMAL CANINE SPERM AFTER ORCHIECTOMY - Armas R., Sandra (2011)
The aim of the study was to determine the maximum time to recover and cryopreservespermatozoa from the tail of canine epididymis post orchiectomy. The testes were obtainedthrough orchiectomy from 20 dogs aged 1 to 8 years. The testis were placed in sodiumchloride 0.9% and stored at 5 °C for 0, 24, 48 and 72 hours. Spermatozoa were recoveredby cutting the tail of the epididymis in an extender based on Tris-citrate-fructose. For the cryopreservation process, egg yolk (20%) and glycerol (5%) was added to the dilutedsample (sperm + dilutor). The new dilution was packaged in 0.5 ml straws, which weresubjected to a cooling curve and then placed in liquid nitrogen. Total motility, progressivemotility and functional integrity of the membrane were evaluated. Beforecryopreservation process, total motility after 24 and 72 hours of storage at 5 ºCdecreased (p<0.05). However, total motility found after cryopreservation process variedsignificantly only after 72 hours of storage at 5 ºC (p<0.05). Similar trend was observedfor progressive motility. The functional integrity of membrane, both before and afterthe cryopreservation process, did not suffer significant changes between groups. Theresults showed that it is possible to collect and cryopreserve epididymal sperm until48 hours of orchiectomy.